Heat transfer in a packed sugar cane bagasse bed - Laurentino, C. L. [UNESP]; Casciatori, F. P. [UNESP]; Thoméo, J. C. [UNESP] (My University, 2008)
Heat transfer in a packed bed of sugar cane bagasse, which is a potential biofuel used in cars and industries, percolated with air flow was studied. The fibers were washed, sieved, oven dried, and afterwards moisture content was adjusted to 4 and 47%. The relative humidity of the air, packing bed technique, and the initial moisture content of the porous media did not have a significant effect on the outlet temperature of the bed. Air flow rate influenced the averaged radial temperature profile, but not the temperature measured at the nearest position to the tube wall. At the end of the experiments, moisture segregation was observed, the lower bed depths being drier than the higher ones. This is an abstract of a paper presented at the 18th International Congress of Chemical Process Engineering (Praque, Czech Republic 8/24-28/2008).